Women Involvement in Terrorism Action in Indonesia - Hagung Prayogo; Fauziyah Aulia Rishanti (SOSHUM : Jurnal Sosial dan Humaniora, 2021)
This research is motivated by the increasing cases of involvement of women in acts of terrorism in Indonesia, the participation of women in acts of terrorism raises anxiety in Indonesian society and shows that currently there is an increase in the development of radicalism against women, they not only act as protectors or protectors but also today. acting as a combatant and being directly involved in acts of terrorism such as being a suicide bomber, this development is a threat that must be overcome by the Indonesian government. This article explains the development of the threat of women's involvement in acts of terrorism in Indonesia and how strategies can be implemented to overcome this. The data in this study came from interviews, documentation, and literature review and sourced from sources such as Densus 88, and BNPT. The results of this study explain that the involvement of women in the activities of radical terrorist groups is a new trend to avoid suspicion by security forces and groups that use the role of women as ISIS groups, several factors influence women to become involved in the actions of radical terrorist groups, namely due to marriage ties, friendship. , as well as social media. To overcome the trend of women being involved in acts of terrorism in Indonesia, several strategies are needed to overcome them: a humanitarian approach, an academic approach, and assistance in increasing literacy for women.